TOXIC IMPACT OF LETHAL AND SUBLETHAL CONCENTRATIONS OF PHORATE ON THE TOTAL PROTEIN LEVELS IN DIFFERENT TISSUES OF COMMON CARP Cyprinus carpio - DR. G. LAKSHMAIAH (International Journal of Pharma and Bio Sciences, 2014)
Fingerlings of Cyprinus carpio were exposed to acute lethal toxicity of Phorate for one day and 4 days and chronic sublethal toxicity of Phorate for 1, 7, 15 and 30 days. After the completion of stipulated exposure period the total protein levels were estimated in the target organs like gill, liver, muscle, kidney and brain of the fish. Significant alterations were observed in the levels of total protein content in all the organs of the fish exposed to both acute lethal and chronic sublethal toxicity of Phorate. The alterations in the levels of total protein content were significantly dose dependent.